Risk Factors of Klebsiella pneumoniae Infections in Pediatric Healthcare Settings - S. A. Kuzmenko; M. A. Shmakova; E. B. Brusina (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. Klebsiella pneumoniae is a major cause of severe healthcare-associated infections in children, representing one of the six most widespread multidrug-resistant microorganisms worldwide and requiring the implementation of population-wide treatment strategies.Aim. To study the risk factors for Klebsiella spread in pediatric healthcare settings.Materials and Methods. Here we performed a descriptive retrospective epidemiological study of Klebsiella spp. cases in pediatric units across the entire Kemerovo region (2012–2019). In total, we documented 27,852 treatment outcomes. We further selected 52 confirmed cases and assessed their risk profiles in comparison with 738 condition-matched control children.Results. Average incidence of Klebsiella spp. detection in pediatric healthcare settings was 78.52 per 1,000 patients (95% CI = 75.42–81.74). We revealed a declining incidence of Klebsiella pneumoniae infection in the region, with notable 4-year cyclicity. The proportion of Klebsiella pneumoniae-infected patients increased 2-fold after 5 days of antibiotic therapy. Among the risk factors of Klebsiella pneumonia infection were artificial feeding (OR = 9,21, 95% = 3,31–35,45, р = 0,0001), assisted ventilation (OR = 7,36, 95% CI = 3,92–14,0], р = 0,0001), use of nebulizers (OR = 5,34, 95% CI =2,49 – 10,9], р=0,0001), airway management (OR = 4,62, 95% CI =2,49–8,56, р = 0,0001), preterm birth (OR = 2,55, 95% CI =1,38 – 4,69, р=0,001), low body weight (OR = 2,48, 95% CI = 1,34–4,56, р = 0,002), enema administration (OR = 1,80, 95% CI = 0,78–3,81, р = 0,088), and nasogastric intubation (OR = 1,79, 95% CI = 0,85–3,54, р = 0,065).Conclusions. The incidence of Klebsiella pneumoniae infections is currently lowering and has 4-year cyclicity. Antimicrobial treatment is associated with 2-fold increased risk if administered for ≥ 5 days. A number of healthcare-associated risk factors of Klebsiella pneumoniae infections have been found.